Risk-Sharing and Student Loan Policy: Consequences for Students and Institutions - Douglas A. Webber (Institute for the Study of Labor (IZA), 2015)
This paper examines the potential costs and benefits associated with a risk-sharing policy imposed on all higher education institutions. Under such a program, institutions would be required to pay for a portion of the student loans among which their students defaulted. I examine the predicted institutional responses under a variety of possible penalties and institutional characteristics using a straightforward model of institutional behavior based on monopolistic competition. I also examine the impact of a risk-sharing program on overall economic efficiency by estimating the returns to scale for undergraduate enrollment (as well as other outputs) among each of ten educational sectors. I find that even a relatively small incentive effect of a risk-sharing would lead to a substantial decline in overall student debt. There is considerable heterogeneity across sectors, with 4-year for-profit institutions accounting for the majority of the savings. My estimates suggest that a risk-sharing program would induce a modest tuition increase, but that there is unlikely to be a substantial loss of economic efficiency in terms of costs due to a reallocation of students across sectors.
Keywords: I22; 330; student loans; higher education; default rates